Effect of Urea and SP-36 on the Growth of Grafted Rubber Seedling (Hevea brasiliensis Muell.Arg.) Clone PB 260 - Helilinawati Helilinawati; Hery Sutejo; Abdul Fatah (Universitas 17 Agustus 1945 Samarinda, 2019)
The aim of research to determine the effect of urea and SP-36 fertilizer as well as their interaction on the graftedrubber seedling growth, and to find appropriate doses of urea and SP-36 fertilizers for better growth of grafted rubber seedlings.The research was conducted from February 2015 until May 2015 in the village of Empas, Sub District of Melak, West Kutai Regency, East Kalimantan Province.The study design used was completely randomized design (CRD) in a factorial 4 x 4, and repeat 3 times, which comprises two factors research. The first factor was Urea (N), consisted of four levels, namely: no urea application or control (n0), 2,5g/polybag (n1), 5g/polybag (n2), and 7,5g/polybag (n3). The second factor was SP-36 fertilizer (P), consisting of 4 levels, namely: no SP-36 fertilizers application or control (p0), 2,5g/polybag (p1), 5g/polybag (p2), and 7,5g/polybag (p3).The results showed that the treatment of urea (N) affects highly significant on the plant height at ages of 2, 3 and 4 months after grafting, number of leaf at 4 months after grafting and stem diameter at 3 and 4 months after grafting. It affected significantly on the number of leaf at 3 months after grafting. But it did not affect significantly on the number of leaf at 2 months after grafting, and stem diameter at 2 months after grafting.SP-36 fertilizer treatments (P) affected very significantlyon the stem diameter at 3 and 4 months after grafting. It affected significantly on the plant height at 4 months after grafting. But it did not affect significantly on the seedling height at 2 and 3 months after grafting, number of leaves at 2, 3 and 4 months after grafting, and stem diameter at 2 months after grafting.The interaction treatment (NXP) affected significantly on the stem diameter at 4 months after grafting. But it did not affect significantly on the seedling height at 2, 3 and 4 months after grafting, number of leaves at 2, 3 and 4 months after grafting, and stem diameter at 2 and 3 months after grafting